2013
DOI: 10.1016/j.jallcom.2013.03.018
|View full text |Cite
|
Sign up to set email alerts
|

Influence of coumarin as an additive on CuO nanostructures prepared by successive ionic layer adsorption and reaction (SILAR) method

Abstract: The effect of coumarin doping during the growth of CuO nanostructures by SILAR method has been studied. It was found that coumarin considerably influences the growth process, manipulates the bandgap and modifies the crystallite size of the films. XRD experiments evidenced that with higher coumarin concentrations in the growth solution, the microstrain and dislocation density increased, while the crystallite size of the films decreased. SEM images revealed that the thicknesses of the plate-like nanostructures d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 22 publications
4
17
0
Order By: Relevance
“…5b). A similar behaviour has been observed in chemically grown copper oxide thin films with coumarin additive by Bayansal et al [20]. They suggested that coumarin as an additive can be …”
Section: Optical Measurementssupporting
confidence: 83%
See 3 more Smart Citations
“…5b). A similar behaviour has been observed in chemically grown copper oxide thin films with coumarin additive by Bayansal et al [20]. They suggested that coumarin as an additive can be …”
Section: Optical Measurementssupporting
confidence: 83%
“…According to Table 1, it can be seen that crystallite size of both as-deposited and annealed films decrease with increasing coumarin content. As reported in literature [19][20][21], coumarin makes the grains smaller and uniform [21]. Thus, the decreasing in the average crystallite size may be attributed to the increasing coumarin presence in the growth solution.…”
Section: X-ray Analysissupporting
confidence: 60%
See 2 more Smart Citations
“…CuO films have been produced by the electro-deposition method [9], wet chemistry [10], sol-gel dip-coating [11] and successive ionic layer adsorption and reaction (SILAR) [12]. As compared to other methods, SILAR offers a very easy, cheap, and efficient strategy which can be performed in low temperatures [13].…”
Section: Introductionmentioning
confidence: 99%